Kegiatan Pengabdian Masyarakat Dalam Rangka Pencegahan Dampak Polusi Udara Kepada Penurunan Fungsi Paru dan Gangguan Penyakit Hematologi - Ernawati Ernawati; William Gilbert Setyanegara; Joshua Kurniawan; Yohanes Firmansyah (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Air pollution is one of the problems in metropolitan cities that will have a major impact on public health. One of the effects of air pollution is a decrease in the quality of lung function accompanied by hematological disease disorders. West Jakarta is one of the areas with the worst air pollution index in Indonesia, even having a figure 6.1 times higher than the threshold set by the World Health Organization. This of course will have an impact on people who often ride motorbikes or public transportation. Therefore it is important to provide knowledge to the public in order to prevent and deal with air pollution so that it does not become a health problem in the future. In addition, it is also important to carry out early detection and screening to overcome health problems that have occurred, such as spirometry and hematological examinations.